Influence of Cigarette Smoking on Rheumatoid Arthritis Risk in the Han Chinese Population - Yin, Jian; He, Dongyi; Jiang, Lei; Cheng, Fang; Guo, Qian; Huang, Shaolan; Zeng, Xiaofeng; Liu, Yi; Brown, Matthew A.; Xu, Huji (Frontiers in Medicine, 2017)
Objectives Cigarette smoking has been shown in European populations to be associated with rheumatoid arthritis (RA) susceptibility. This study aims to examine the association of smoking with RA in the Han Chinese population. Methods 718 Han Chinese RA patients and 404 healthy controls were studied. The associations of cigarette smoking (current, former or ever vs. never smokers, and pack-years of exposure) with RA, anti-cyclic citrullinated peptide antibody (ACPA) positive RA, IgM rheumatoid factor (RF) positive RA, and baseline radiographic erosions (modified van der Heijde-Sharp scores), were assessed. The interaction between smoking and the HLA-DRB1 shared epitope (SE) in RA was also examined. Results In this study, 11 (1.53%) cases and 6 (1.49%) controls were former smokers (p=0.95) while 95 (13.23%) cases and 48 (11.88%) controls were current smokers (p=0.52). Trends towards associations between smoking status (ever vs. never) with RA overall (p=0.15, OR=1.44), ACPA-positive RA (p=0.24, OR=1.37), RF-positive RA (p=0.14, OR=1.46), or the presence of radiographic erosions (p=0.66, OR=1.28) were observed although individually here were not statistically significant. There was no evidence of statistical interaction between smoking status (ever vs. never) and SE for all RA, ACPA-positive RA, ACPA-negative RA, RF-positive RA, RF-negative RA (p=0.37, 0.50, 0.24, 0.26, 0.81 respectively), and the 95% CI for the AP for all interactions included zero. Conclusion This is the first study to examine the association of cigarette smoking with RA in the Han Chinese population. This study shows a trend towards an interaction between smoking and SE carriage influencing the risk of RA, though findings were not statistically significant. It is possible that in the presence of universal exposure to heavy air pollution the effect of smoking on RA risk may be obscured.